The relationship between the Quasi Biennial Oscillation and Sunspot Number - Sagir, Selcuk; Karatay, Secil; Atici, Ramazan; Yesil, Ali; Ozcan, Osman (Elsevier Sci Ltd, 2015)
In this study, the relationship between the monthly mean values of the Quasi Biennial Oscillation (QBO) measured at 10 hPa and 70 hPa altitudes and Sunspot Number (SSN) for solar maxima and solar minima conditions is analyzed. Before applying the model for the statistical analysis of the study, the stationary of the variables is investigated by using the unit root test. Existence of a long-term relationship between the variables is also investigated by using the co-integration test. Positive and negative relationships between SSN and QBO obtained for 10 hPa and 70 hPa are observed for the solar maxima and the solar minima, respectively. The explainable effects of the SSN on the QBO at 10 hPa altitude are greater than those at 70 hPa. When the calculated coefficients are analyzed, it is observed that the variation of QBO up to 16 m/s is due to SSN. The rest of at least 34 m/s are seen to be based on the other variables. (C) 2014 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Quasi Biennial Oscillation; Sunspot Number; Multiple regression